The Missing Point Between Strategic Supplier Evaluation and Integration: A Dyadic Case Study - Matlejewski, Piotr (Journal of Positive Management, 2023)
Purpose: The aim of this study is to explore the reasons for a supplier’s sudden withdrawal from cooperation and thus to identify the missing element in the commonly used supplier evaluation frameworks that determines the possibility of future dyadic integration in the supply chain. Academic literature very often moves from supplier evaluation to strategic collaboration without considering the activities between the two. Methodology: The paper is based on a case study of customer-supplier dyad of manufacturing companies. Based on the Purchasing Portfolio Matrix and the ‚Dutch windmill’ concept, the case of supplier-customer relationship termination was investigated. Findings: The study revealed that there should be an intermediate step between strategic supplier evaluation and the transition to strategic cooperation. The customer was conducting an elaborate evaluation of the supplier without being interested in how he was evaluated by his vendor. The findings indicated the need for customers to learn about the criteria and rating level given by strategic suppliers, also in relation to the ratings given to other customers. Originality/value: The paper provides valuable practical implications that should help customers avoid problems with suppliers and, in the worst case scenario, better prepare for the end of the relationship. To generate these, a fairly uncommon research approach was used - the dyadic approach in supply chain integration management.